Democracy and Development in Africa: Demystifying Democracy as the Best Form of Government - Nwokedi, Michael Eberechukwu; Obasi, Christopher Uchenna (Journal of Contemporary International Relations and Diplomacy, 2024)
The resurgence of coups d’etat in Africa has resuscitated discussions about the suitability of democracy as an agent of development on the Continent. The dominant impression in extant literature suggests that the inefficiencies of democratic regimes provide the attractive invitation to military rule. Despite the encomiums showered on democracy as the global best form government, many years of its practice in Africa have resulted in massive underdevelopment. It has not delivered on its promise of free and fair elections, freedom of the press, association and others. Under the watch of democracy, many African countries have transited from one-party to dominant-party states while rigging and related electoral vices continue to fester. Police brutality and human rights abuses are rampant while insecurity and inequality have reproduced themselves in many forms. This paper contends that democracy is culpable in the business of stifling development in Africa hence, the complexity and continuity of Africa’s crisis of underdevelopment questions the validity of Western imposition of Democracy as the best form of government. It adopts an amalgam of the Liberal Democratic and Centre-Periphery Models to situate the failure of democracy in Africa within the context of metropolitan interference in African politics, with attendant African petit bourgeois attachment to foreign finance capital. Consequently, it denounces democracy as the best form of government and insists that Africa’s best form of government is that which arises out of her sociological experience and censorship to address critical aspects of her political economy.